Pengembangan Sumber Daya Manusia di Sekretariat Daerah Kabupaten Tanggamus - Ardiansyah, Zeky; Wiranida, Wiranida; Juwita, Masayu Nila; Malik, Malik; Purnomo, Agus (Universitas Bandar Lampung (UBL), 2024)
Human resource development at the Regional Secretariat of Tanggamus Regency has not been optimally implemented by each section, as evidenced by the infrequent organization of training, seminars, and employee participation policies that are conducted in a simple manner without staged and continuous planning, even though these needs are urgent. This study uses a qualitative method, with data collection techniques including observation, interviews, and documentation, while data analysis techniques involve data reduction, data presentation, and conclusion drawing. The research results indicate that human resource development at the Regional Secretariat of Tanggamus Regency has been carried out through job rotations across departments to enhance experience and understanding of responsibilities, educational orientation training for employees in both formal and non-formal contexts, and leadership guidance aimed at improving employee performance, although such guidance has not been fully absorbed by some employees. Job rotation aids employees in understanding new responsibilities, while formal and non-formal training provides opportunities to enhance their competencies, yet leadership directions to employees still require improvement to be more effective. Therefore, leadership attention to human resource development through job rotation, training, and guidance needs to be enhanced and carefully re-planned to ensure that human resource development implementation significantly impacts employee performance improvement.